Effects of kangaroo mother care combined with nurse-assisted mindfulness training for reducing stress among mothers of preterm infants hospitalized in the NICU: a randomized controlled trial - Xia Ouyang; Xin Ye; Xianping Liu; Haihong Zhang; Shaoru Huang; Yanfang Fan; Yunfeng Lin (BMC, 2024)
Abstract Background Kangaroo mother care (KMC) can have a positive effect on the mental well-being of a mother. However, there are specific challenges associated with the process that may contribute to increased anxiety for the mother. By integrating nurse-assisted mindfulness training alongside KMC guidance, nurses may effectively alleviate maternal stress to a greater extent. Methods A single-centre randomized controlled trial was conducted to investigate the effects of KMC combined with nurse-assisted mindfulness training. The study included preterm infants with a gestational age of less than 32 weeks or a birth weight of less than 1500 g and their mothers, who were randomly divided into two groups. The intervention group consisted of mothers who received KMC combined with nurse-assisted mindfulness training for 14 days. The control group comprised mothers who received only KMC for 14 days. Data from both groups were collected and compared for analysis. Results Forty-seven infants and their mothers were included in the intervention group, whereas 44 pairs were included in the control group. After the intervention, the parental stressor scale scores for the neonatal intensive care unit (PSS: NICU) (3), PSS: NICU (4), and Hospital Anxiety and Depression Scale (HADS) scores for the intervention group were lower than those for the control group, whereas the Five Facet Mindfulness Questionnaire (FFMQ) (1), FFMQ (4), and FFMQ (5) scores for the intervention group were higher. The degree of change in the PSS: NICU and HADS scores was inversely correlated with the degree of change in the FFMQ score. The breast milk feed rate and weight gain rate were greater in the intervention group than in the control group. No adverse reactions were observed in either group. Conclusions Kangaroo mother care combined with nurse-assisted mindfulness training is an acceptable, feasible, and effective procedure for reducing anxiety in mothers of preterm infants in the NICU, with potential benefits for the short-term prognosis of these infants. Trial registration Chinese Clinical Trial Registry, ChiCTR1900023697, registered on June 8, 2019, retrospectively registered.